Exploring the Influence of Achievement Goals on Exercise Motivation: A Systematic Review - Xiaofei Lin,; Nasnoor Juzaily bin Mohd Nasiruddin,; Soh Kim Geok, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Recent scholarly work has emphasized the significance of achievement goals in influencing exercise motivation, yet their impact in this context remains insufficiently explored. This review systematically investigates the effects of achievement goals on diverse facets of exercise motivation, encompassing performance, achievement, and engagement. Adhering to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines, our study utilized the Web of Science (WoS) database, culminating in the inclusion of 21 out of 478 scrutinized papers that met all stipulated inclusion criteria. Our findings elucidate that achievement goals, specifically mastery orientation, self-orientation, and task-orientation, exert a positive influence on exercise motivation, spanning the realms of performance, engagement, and achievement. Nevertheless, an excessive emphasis on the avoidance dimensions of these goals may detrimentally impact motivation. To optimize exercise outcomes and bolster motivation, physical education instructors should implement interventions aimed at assisting students in navigating their achievement goals. Strategies encompassing pedagogical methodologies, technological support, and therapeutic approaches may prove advantageous. Future research endeavours should delve into potential variables, both environmental and personal, that could mediate the relationship between achievement goals and exercise outcomes.